Philosophy of mathematics: An introductory essay - Korner, Stephan (London Hutchinson University library, 1960)
Concise, accessible sketches of the views of Plato, Aristotle, Leibniz, and Kant highlight this study of the general structure and foundation of pure and applied mathematics. Author Stephan Körner dedicates two chapters apiece &; one expository and one critical &; to each of the three main modern schools of thought on mathematical philosophy: the formalists, the logicists, and the intuitionists.
Keywords: Mathematics essay; Mathematics philosophy; Mathematics